2018
DOI: 10.1007/s10238-018-0492-7
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatosis with polyangiitis: clinical course and outcome of 60 patients from a single center in South India

Abstract: Granulomatosis with polyangiitis (GPA) previously known as Wegener's granulomatosis is one of the forms of idiopathic systemic vasculitis. There is very scanty data available on GPA in Asian and Indian population. We studied data of 60 patients from southern India, diagnosed with GPA to describe the physical characteristics, the treatment, and outcome. Patients who fulfilled any two of the four criteria proposed by the American College of Rheumatology, and those with clinical features of GPA with ANCA positivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…We observed that the excess mortality of GPA was extremely high within the first year, particularly the first 6 months after diagnosis, compared to the matched comparison cohort. Previously published clinic-epidemiologic studies regarding GPA in Japan, Korea, and other Asian countries did not report timing of death or mortality risk stratified by follow-up duration due to limited sample size or insufficient tracking time ( 7 , 10 , 15 ). A pooled analysis from randomized clinical trials documented that the causes of death in GPA differ in patients with early death compared to those with late death ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the excess mortality of GPA was extremely high within the first year, particularly the first 6 months after diagnosis, compared to the matched comparison cohort. Previously published clinic-epidemiologic studies regarding GPA in Japan, Korea, and other Asian countries did not report timing of death or mortality risk stratified by follow-up duration due to limited sample size or insufficient tracking time ( 7 , 10 , 15 ). A pooled analysis from randomized clinical trials documented that the causes of death in GPA differ in patients with early death compared to those with late death ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawal of glucocorticoid therapy has been identified as a strong predictor of relapse; therefore, it is common practice to keep patients on low doses of prednisone (or equivalent) as part of the maintenance regimen. AZT, MTX, and mycophenolate mofetil have proven to be as effective as CYC for AAV maintenance therapy in randomized trials (Table 3) (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] Relapses were defined as recurrence of GPA of sufficient severity that required treatment or increase in the dose of treatment on a previously stable patient. [ 4 ] Diminution of vision was defined as a decrease in visual acuity by two Snellen lines or more. An increase in visual acuity by two Snellen lines or more after resolution of the scleral inflammation clinically was denoted as improvement of vision.…”
Section: Methodsmentioning
confidence: 99%
“…It mainly affects the upper and lower respiratory tracts and kidneys. [ 3 4 ] Limited GPA usually spares the kidneys. Ocular GPA without respiratory and renal involvement is classified as very limited form of GPA.…”
mentioning
confidence: 99%